Effects of gold nanoprism-assisted human PD-L1 siRNA on both gene down-regulation and photothermal therapy on lung cancer. (November 2019) - Liu, Bin; Cao, Wen; Qiao, Guanglei; Yao, Shanying; Pan, Shaojun; Wang, Lirui; Yue, Caixia; Ma, Lijun; Liu, Yanlei; Cui, Daxiang
Graphical abstract: Abstract: Gold nanoprisms (GNPs) have been broadly studied for the potential applications in both imaging and treatment on tumors due to their special characteristics. Herein we reported that a new nanoplatform GNPs@PSS/PDADMAC-siRNA (GNPs-siRNA) was designed and fabricated by sequentially coating the GNPs with poly (sodium 4-styrenesulfonate) (PSS) and poly (-diallyldimethylammonium chloride) (PDADMAC) to carry small interfering RNA (siRNA). Human program death-ligand 1 (PD-L1) was recently known to be crucial for cancer cell survival through the intrinsic signaling activities, besides serving as an important checkpoint gene in immune system. We successfully attached the human PD-L1 siRNA to the surface of GNPs@PSS/PDADMAC to obtain the GNPs-hPD-L1 siRNA nanoplatform. Real Time Cellular Analysis (RTCA) assay demonstrated that GNPs-hPD-L1 siRNA exhibited remarkable capacity to inhibit the proliferation of human lung cancer cells. Subsequent in vitro and in vivo experiments verified that the GNPs-hPD-L1 siRNA not only functioned as a carrier for siRNA delivery to down-regulate the hPD-L1 expression, but also served for photoacoustic (PA) imaging and photothermal agents for photothermal therapy (PTT) in both human lung cancer cells and human lung cancer cells-derived tumors. Our findings could be expected to provide an innovative direction for future clinical transformation application. Statement of Significance: To our knowledge, this is the first paper related to the hPD-L1 siRNA delivery combined with the gold nanoparticles, especially the gold nanoprisms. The as-prepared GNPs-hPD-L1 siRNA nanoplatform not only functioned as a carrier for siRNA delivery to down-regulate the PD-L1 expression, but also acted as photothermal agents for theranostic effects in both human lung cancer cells and human lung cancer cells-derived tumors. The as-prepared GNPs-hPD-L1 siRNA nanoplatform could knock down human PD-L1 gene expression, which caused the inhibition on proliferation of human lung cancer cell in vitro or in vivo . The as-prepared GNPs-hPD-L1 siRNA nanoplatform possessed excellent photoacoustic imaging ability and photothermal therapy effects.